2001
DOI: 10.1094/phyto.2001.91.7.673
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Specific Apple Root Pathogens by Brassica napus Seed Meal Amendment Regardless of Glucosinolate Content

Abstract: The impact of Brassica napus seed meal on the microbial complex that incites apple replant disease was evaluated in greenhouse trials. Regardless of glucosinolate content, seed meal amendment at a rate of 0.1% (vol/vol) significantly enhanced growth of apple and suppressed apple root infection by Rhizoctonia spp. and Pratylenchus penetrans. High glucosinolate B. napus cv. Dwarf Essex seed meal amendments did not consistently suppress soil populations of Pythium spp. or apple root infection by this pathogen. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
133
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 25 publications
(35 reference statements)
8
133
0
1
Order By: Relevance
“…and the nematode Pratylenchus penetrans, but did not consistently suppress soil populations of Pythium spp. and control apple root infection (Mazzola et al 2001). Mazzola (2007) suggested that the role of the isothiocyanates could be mediated by select groups of indigenous populations of microorganisms whose presence and sufficient population density are necessary to achieve disease control.…”
Section: Biofumigation or Biodisinfectionmentioning
confidence: 99%
“…and the nematode Pratylenchus penetrans, but did not consistently suppress soil populations of Pythium spp. and control apple root infection (Mazzola et al 2001). Mazzola (2007) suggested that the role of the isothiocyanates could be mediated by select groups of indigenous populations of microorganisms whose presence and sufficient population density are necessary to achieve disease control.…”
Section: Biofumigation or Biodisinfectionmentioning
confidence: 99%
“…Brassicaceae seed meal amendments have demonstrated the capacity to suppress various components of the pathogen complex that incites apple replant disease, including Rhizoctonia solani and Pratylenchus penetrans (21,22). In contrast, the diverse populations of Pythium spp.…”
mentioning
confidence: 99%
“…In contrast, the diverse populations of Pythium spp. that contribute to this disease phenomenon is stimulated by soil amendment with seed meals of Sinapis alba or low glucosinolate-containing cultivars of Brassica napus (4,20,21), thus placing limits on the utility of this approach for disease control. An integrated system which employs a post-plant application of mefenoxam in concert with pre-plant seed meal amendment is a viable control practice in conventional orchard production (22), but is not compatible with organic production systems.…”
mentioning
confidence: 99%
“…Glucosinolates and their degradation products do not, however, solely explain the allelochemical effects of Brassica species in crop rotations and some caution should be paid in application of brassica seed meal, since at high concentrations (2% vol/vol) it can be phytotoxic, for example to apple (Malus )domestica Borkh.) (Mazzola et al, 2001).…”
Section: Consideration Of the Biofumigation Potentialmentioning
confidence: 99%